Pengembangan Portal Wonogiri Explore Guna Mendukung Pariwisata Cerdas Kabupaten Wonogiri - Khoirun Nisa; Muhammad Rizal Fernandita Pamungkas; Fera Tri Wulandari (LPPM Universitas Flores, 2026)
Wonogiri Regency has great tourism potential that covers nine destination categories, including Reservoirs and Dams, Caves, Waterfalls, Museums and Education, Heritage and Culture, Beaches, Hills and Mountains, Lakes and Springs, and Recreational Tourism. However, this potential is not yet supported by an integrated digital information platform, so tourists have difficulty exploring destinations and obtaining complete information. This study aims to design and implement Wonogiri Explore as a web-based Geographic Information System (WebGIS) for Wonogiri Regency tourism that integrates interactive maps, destination directories, tourist reviews, and TIC Online. The system was developed using the Waterfall model with five stages, namely analysis of needs, design, implementation, testing, and maintenance. Research methods include observation, interviews, literature studies, and documentation. The system was built using the CodeIgniter 3 framework with a Model-View-Controller (MVC) architecture, a MySQL database with nine relational tables, and the Leaflet.js library with OpenStreetMap integrated with the Leaflet Routing Machine plugin. Key features include an interactive map with category-based markers, a destination detail page with photo gallery, a review and star rating system, a category filter feature, and a TIC Online widget with real-time live chat using a cookie mechanism. Black Box Testing included 33 test scenarios across eight feature groups and White Box Testing included 18 critical logic paths across four main controllers, both achieving a 100% success rate. The Wonogiri Explore system is expected to increase the visibility of Wonogiri Regency's tourist destinations and support the realization of sustainable smart tourism.